Happy Dreamer - Reynolds, Peter H. 1961- (Peter Hamilton) (New York : Orchard Books, an imprint of Scholastic Inc., 2017)
A "dreamer maximus" describes the many ways one can dream, and the importance of being a happy dreamer.
Accelerated Reader AR